Effect of ion beam current on dust charge fluctuations and ion-acoustic waves in electronegative dusty plasmas. (6th December 2021) - Basnet, Suresh; Maskey, Anish; Deuja, Atit; Khanal, Raju
Abstract: The effects of ion beam current associated with the streaming positive ions on the dust charge fluctuations and ion acoustic wave propagation in quiescent electronegative dusty plasma have been investigated using fluid theory. The dust charging phenomenon and unstable mode of ion waves are modified for two streaming conditions of positive ions which are extended and graphically illustrated. The dependencies of the growing and damping rate of ion waves on dust density and the size of dust grains are studied. The evolution of dust surface potential is found in the negative domain with the increase in concentration of negative ions and the instability rate for ion wave decreases. Furthermore, it is shown that the dust surface potential shifts into positive domain as the electrons are significantly depleted (and the plasma becomes ion-ion plasma) from the electronegative plasma and thus ion waves exhibit a damping phenomenon.